Development of software for effective measurement of the moisture content of the plastic mass coming out of the filter press - Burxonov Dovron Abdujalol oʻgʻli; Joniqulov Egamberdi Shavkat o‘g‘li; Ismatova Ozoda; Maxkamov Xusniddin Bobojon o‘g‘li (Zien Journals, 2023)
In this article, the effectiveness of measuring the moisture content of the viscous mass coming out of the filter press using arduino uno and the FC-28 sensor was determined, and the scheme and software were developed
Keywords: using; sensor; measuring; software